Efficient soft x-ray sources from laser-irradiated gold foam targets with well-controlled impurities. (29th November 2017) - Dong, Yunsong; Yang, Jiamin; Song, Tianming; Shang, Wanli; Zhang, Lu; Huang, Chengwu; Zhu, Tuo; Zhang, Wenhai; Li, Zhichao; Zhan, Xiayu; Du, Huabing; Wang, Feng; et al.
Abstract: As an important x-ray source, enhancement of x-ray emissions from laser-produced plasmas is significant for various applications. Due to less expanding kinetic loss, gold foam with low initial density can have an enhanced x-ray conversion efficiency compared with solid-density gold. However, low- Z impurities within gold foam targets will diminish the enhancement remarkably, and should be tightly controlled. This paper presents an experimental study of a high brightness laser plasma soft x-ray source, based on a 0.36 g c m − 3 gold foam target with negligible impurities irradiated by nanosecond laser pulses with power density around 3  ×  10 14 W c m − 2 at the Shenguang II laser facility. A conversion efficiency, from multi-eV to multi-keV, of 51.2 % is achieved in the x-ray emissions—about 21% relative enhancement compared with a solid-density gold target, and the highest conversion efficiency for Au foam planar targets yet. Good agreement has been achieved between the semi-analytical model prediction and the experimental results.